2019
DOI: 10.1111/gcb.14865
|View full text |Cite
|
Sign up to set email alerts
|

Interface processes between protected and unprotected areas: A global review and ways forward

Abstract: Land‐use changes and the expansion of protected areas (PAs) have amplified the interaction between protected and unprotected areas worldwide. In this context, ‘interface processes' (human–nature and cross‐boundary interactions inside and around PAs) have become central to issues around the conservation of biodiversity and ecosystem services. This scientific literature review aimed to explore current knowledge and research gaps on interface processes regarding terrestrial PAs. At first, 3,515 references related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 112 publications
0
11
0
1
Order By: Relevance
“…Our novel application of the systematic review process has produced results that build on many previous works (e.g., Abell et al, 2017;Dudgeon et al, 2006;Fiedler & Karieva, 1997;Finlayson et al, 2018;Reis et al, 2017;Strayer & Dudgeon 2010) and our eight lessons reiterate and reinforce their essential messages. They complement the findings of a similar review of terrestrial protected area effectiveness, in particular the influence of human activities on biodiversity and governance issues (Blanco et al, 2019). The review has revealed evidence from quantitative case studies that not all protected areas have been effective for freshwater biodiversity conservation.…”
Section: Discussionmentioning
confidence: 65%
“…Our novel application of the systematic review process has produced results that build on many previous works (e.g., Abell et al, 2017;Dudgeon et al, 2006;Fiedler & Karieva, 1997;Finlayson et al, 2018;Reis et al, 2017;Strayer & Dudgeon 2010) and our eight lessons reiterate and reinforce their essential messages. They complement the findings of a similar review of terrestrial protected area effectiveness, in particular the influence of human activities on biodiversity and governance issues (Blanco et al, 2019). The review has revealed evidence from quantitative case studies that not all protected areas have been effective for freshwater biodiversity conservation.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, most studies that assess the relevance of PAs mostly focus on ‘outside’ vs. ‘inside’ comparisons, neglecting the importance of the edge effect (Herremans & Herremans‐Tonnoeyr, 2000). These border areas represent contact zones between protected and unprotected areas containing a vast range of interactions between nature and people (Blanco et al, 2019) and biodiversity should also be evaluated here.…”
Section: Introductionmentioning
confidence: 99%
“…The Global South, particularly the tropics, is home to many biodiversity hotspots and presents opportunities for large‐scale conservation (Brooks et al, 2006). Despite their high level of biodiversity, tropical regions are underrepresented in many aspects of ecological research including reviews of species' responses to climate change (Feeley, Stroud, & Perez, 2017), protected areas research (Blanco et al, 2020), and in biodiversity/ecosystem function (Clarke, York, Rasheed, & Northfield, 2017). Even within the tropics, there are publishing biases, for example, research locations in coral reef studies are positively correlated not with diversity, but with per capita income (Fisher et al, 2011).…”
Section: Introductionmentioning
confidence: 99%